2022
DOI: 10.18632/aging.204448
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the FOX family for predicting kidney renal clear cell carcinoma prognosis and the oncogenic role of FOXG1

Abstract: Previous studies have confirmed that the forkhead box (FOX) superfamily of transcription factors regulates tumor progression and metastasis in multiple cancer. The purpose of this study was to develop a model based on FOX family genes for predicting kidney renal clear cell carcinom (KIRC) prognosis. We downloaded the transcriptional profiles and clinical data of KIRC patients from the Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) datasets. To build a new prognosis model, we scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…confirmed that FOXD1 may be dynamically regulated during kidney injury and repair in the developing mouse model ( 38 ). Previous studies established connections between FOXD1 and kidney tumor development, as well as mitochondrial metabolism ( 39 ). FOXD1 was additionally underscored to promote cell proliferation by targeting the sonic hedgehog pathway and cyclin-dependent kinase inhibitors ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…confirmed that FOXD1 may be dynamically regulated during kidney injury and repair in the developing mouse model ( 38 ). Previous studies established connections between FOXD1 and kidney tumor development, as well as mitochondrial metabolism ( 39 ). FOXD1 was additionally underscored to promote cell proliferation by targeting the sonic hedgehog pathway and cyclin-dependent kinase inhibitors ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…These assays were performed according to our previous studies ( 7 , 17 , 24 ). The primer sequences for qRT-PCR analysis were listed in Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“…CCK-8 and colony formation assays were used to evaluate cell proliferation. For the CCK-8 assay, cells were seeded and cultured in 96-well plates for 48 h. The culture medium was replaced with CCK-8 solution, and the absorbance was measured at 450 nm after 4 h of incubation at 37 °C [ 22 ]. For the colony formation assay, cells were incubated in a 60-mm dish for two weeks and then fixed with paraformaldehyde for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Wound-healing and transwell Matrigel invasion assays were employed to assess cell migration and invasion, respectively. Detailed procedures have been reported in our previous studies [ 3 , 22 ]. Briefly, for the wound-healing assay, a wound was made with a 200 µL pipette tip, and the wound areas were photographed every 3 h to record cell migration.…”
Section: Methodsmentioning
confidence: 99%